2020
DOI: 10.1039/d0ta04089d
|View full text |Cite
|
Sign up to set email alerts
|

A “boxes in fibers” strategy to construct a necklace-like conductive network for high-rate and high-loading lithium–sulfur batteries

Abstract: Following a “boxes in fibers” strategy, a 3D conductive network is constructed by necklace-like N-doped carbon nanofibers with carbon nanoboxes and TiC as an efficient sulfur host, showing excellent performance even under high-rate and high-loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…For addressing the issues above, promising sulfur hosts have been designed to construct advanced LSBs. Because of possessing nanopores, the conductive carbon host such as the carbon nanotube, , the carbon nanorod, , carbon spheres, and graphene , can physically restrict LPSs from escaping to the electrolyte. However, the stability of these carbon-based sulfur electrodes decays obviously during long-term cycling, mainly resulting from friable interactions between polar LPSs and nonpolar carbon. Therefore, various polar materials such as metal oxides, metal sulfides, metal nitrides, metal carbides, , and heteroatoms ,, have been introduced into carbon materials to overcome the mentioned problems and improve the cycling stability based on their strong interaction with LPSs. Thus, combining the anchoring effects of these polar materials and the conductivity of carbon materials, the polysulfides can be fixed and reduced efficiently, resulting in high sulfur utilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For addressing the issues above, promising sulfur hosts have been designed to construct advanced LSBs. Because of possessing nanopores, the conductive carbon host such as the carbon nanotube, , the carbon nanorod, , carbon spheres, and graphene , can physically restrict LPSs from escaping to the electrolyte. However, the stability of these carbon-based sulfur electrodes decays obviously during long-term cycling, mainly resulting from friable interactions between polar LPSs and nonpolar carbon. Therefore, various polar materials such as metal oxides, metal sulfides, metal nitrides, metal carbides, , and heteroatoms ,, have been introduced into carbon materials to overcome the mentioned problems and improve the cycling stability based on their strong interaction with LPSs. Thus, combining the anchoring effects of these polar materials and the conductivity of carbon materials, the polysulfides can be fixed and reduced efficiently, resulting in high sulfur utilization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the stability of these carbon-based sulfur electrodes decays obviously during longterm cycling, mainly resulting from friable interactions between polar LPSs and nonpolar carbon. 23−25 Therefore, various polar materials such as metal oxides, 26−32 metal sulfides, 33−39 metal nitrides, 40 metal carbides, 41,42 and heteroatoms 3,43,44 have been introduced into carbon materials to overcome the mentioned problems and improve the cycling stability based on their strong interaction with LPSs. Thus, combining the anchoring effects of these polar materials and the conductivity of carbon materials, the polysulfides can be fixed and reduced efficiently, resulting in high sulfur utilization.…”
Section: Introductionmentioning
confidence: 99%
“…19 Besides, to achieve a better adsorbing effect, polar additives would be a good choice. Most recently, Wang et al 20 reported a "boxes in fibers" strategy by using hollow carbon nanoboxes and TiC nanoparticles as the sulfur host, which could exhibit excellent rate performance. Yang et al 21 also reported a twinborn TiO 2 −TiN heterostructure to achieve high trapping efficiency of polysulfides by chemical binding, which is also demonstrated by theoretical calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, superior cycling stability over 400 cycles could also be achieved in the high sulfur loading of 5.0 mg cm −2 . Recently, Zhou et al [78] reported a similar templateengaged electrospinning strategy and constructed 3D conductive network composite (CNB-TiC@CNF) with a novel "boxes in fibers" structure. The cubic Fe 2 O 3 nanocubes served as a template and played a key role in building isolated hollow carbon nano boxes along the nanofibers.…”
Section: Composite Carbon Nanofibersmentioning
confidence: 99%